Anthracite coal-based activated carbon for elemental Hg adsorption in simulated flue gas: Preparation and evaluation. (1st September 2020) - Song, Guanrong; Deng, Ruoqi; Yao, Zheng; Chen, Huazhi; Romero, Carlos; Lowe, Tom; Driscoll, Greg; Kreglow, Boyd; Schobert, Harold; Baltrusaitis, Jonas
Abstract: Mercury (Hg) is one of the major airborne emissions from coal combustion sources. Mercury emissions can be a serious pollution issue that is harmful to human health. Activated carbon (AC) is one of the most promising sorbents for Hg adsorption to date. Due to its high cost of chemical preparation, an affordable alternative activated carbon with a high Hg-capturing capacity would be beneficial to environmental security. This study focused on investigating the use of anthracite coal-based activated carbon (ACAC) prepared by a chemical activation method to remove elemental Hg from simulated flue gas. An activation process was developed by evaluating different carbonization temperatures, reagent/coal mass ratios and treating environments. The sample with the highest surface area was selected for synthesizing a bromide-impregnated ACAC. The ACAC sample prepared with KOH at a carbonization temperature of 800 °C, KOH/anthracite mass ratio of 1:1, and activated in an N2 environment yielded a surface area of 527.43 m 2 /g. Mercury adsorption experiments using synthesized ACAC in simulated flue gas were conducted at two different temperatures, 20° and 100 °C, with exposure times of 2.5 and 1 h, respectively. The kinetic adsorption capacity was found to increase with decreasing temperature. Specifically, at the Hg-laden gas temperature of 20 °C, with 2.5 h exposure time, the adsorbent can achieve the maximum adsorption capacity of 476.51 μ  g/g. The bromide-impregnated ACAC was also investigated under two different temperatures of 20 °C and 100 °C and exposure of 5 h. The adsorption capacity of the bromide-impregnated ACAC was found to be higher at elevated temperatures.